The Effect of Flashcards in Online-Based Maharah Kitabah Learning on Learning Outcomes - Norhidayah Norhidayah; Rosita Ilhami; Zahrotunnida Zahrotunnida; Nurlaila Nurlaila (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
Writing is an essential skill taught in learning Arabic. Learning Arabic writing skills online often seems monotonous, so students feel bored. It will impact the mastery of the material the lecturer presents and the skills in writing Arabic. Therefore, it takes a medium from an image so that students can express ideas to compose an article that fits the specified theme. This study aims to determine the effect of flashcards in online-based Maharah Kitabah learning on student learning outcomes at IAIN Palangka Raya. This study used a quantitative method with a descriptive approach. The subjects were 23 students of IAIN Palangka Raya. Data collection techniques used were questionnaires and documentation. The data collected was then analyzed using SPSS. The study results indicated that there was an influence of flashcards in online-based Maharah Kitabah learning on student learning outcomes at IAIN Palangka Raya. Students are invited to master the material using this media, both in theory and practice, since flashcards emphasize practicing rather than just delivering material. Consequently, using this media effectively increases interest in Maharah Kitabah learning.